Recognition of Lao sentence sign language using kinect sensor - Sombandith, Vimonhak; Walairacht, Aranya; Walairacht, Somsak (My University, 2017)
This paper presents a technique for recognition Lao sentence sign language by using a Kinect sensor. By using Kinect sensor, feature joint positions of human body can be tracked. After that the joint angles between each pair of joint vectors of adjacent joint positions are measured. When the user perform a series of posture representing a simple sentence of Lao sign language, the system records joint angles that is significantly changed from one posture to another posture. Feature joint angles stored in the database is used to recognition the testing sentence's posture. The recognition rate of about 75% is achieved from the experiments performed 10 simple sentences of Lao sign language.
Keywords: joint position; kinect sensor; Lao sentense sign language; Skeleton detection